Soil morphological characteristics in the active volcanic toposequence zone at Tangkuban Parahu volcano, Indonesia - Hakim, Dani Lukman; Machalett, Bjoern; Adji, Riyanto; Satwhikawara, Rachmi; Alam, Syamsu (Universitas Lancang Kuning, 2024)
Soil formation in volcanic terrains presents a significant challenge due to the diverse physical and chemical properties imparted by volcanic activity, which are not yet fully understood. This study investigates the unique morphological characteristics of soil profiles within crater topography sequences at the Tangkuban Parahu Volcano, Indonesia. To address this gap, five representative sample profiles (I, II, III, IV, V) were analyzed. The Ratu Crater pathway topography was characterized by steep to very steep slopes. Detailed analysis identified three predominant soil layers, each with distinct features such as color, texture, porosity, and chemical composition, reflecting different stages of soil formation. At the highest elevation near the crater rim, Profile V was composed mainly of volcanic ash, with a loose structure, high porosity, and acidic pH, indicative of recent volcanic deposits. Profile III, at intermediate elevations, consisted of highly weathered soil with sandy loam textures and clear layer demarcations, suggesting prolonged soil development and consolidation. Profile I, at the lowest elevation, featured loamy sand with significant weathering and organic matter incorporation, indicating advanced soil development stages. The findings underscore the impact of volcanic activity on soil morphology, revealing distinct layers that correlate with various ages and developmental stages. Understanding these processes can inform agricultural practices.